Mechanisms of self-regulation of the development of natural populations of Homogyne alpina (L.) Cass. (Asteraceae) in the Carpathians (CHORNOMORSKI BOTANICAL JOURNAL, 2020)
The article summarizes the results of population analysis that were proved on the test platform of the biological laboratory of the Institute of Ecology named by K.A. Malinowski in Carpathians Mountains. Since 1974, the authors conducted stationary observations and field experiments in populations of Homogyne alpina (L.) Cass, at an altitude of 920–2050 m above the sea level. Preconditions causing the emergency of the multivariate phenomenon of plant population development in different ecological-coenotic situations are discussed. There are convincing arguments that multivariate is the result of adaptive transformations. There are operative changes of partial strategies of populations under the influence of natural and anthropogenic factors on these principles. To our opinion, there isn`t multivariance at the level of vitality groups. Accordingly, in each of the three vitality groups are implemented its specific and qualitatively unchanged basic variant in the whole range of H. alpina. The population of H. alpina contain one, two or all three vitality synthogenesis schemes depending on the presence of types of vitality groups. The priority can be given to any of these vital groups, depending on their numerical composition. Authors propose to label each of these groups with an appropriate color based on the RGB color separation principle. It allows creating color markers for prosperous, equilibrium or depressed population that are easy to expert assessments of their viability and perspective for self-healing. The possibility of using computer models for H. alpina synthogenesis algorithms in the vital groups are discussed. The results of experiments with the computer model are presented. Authors concluded, that an incomplete set of vitality schemes occurring in suboptimal conditions limits the range and plasticity of changes in self-support strategies of H. alpina population and increases the risk of their systemic degradation. The interpretation of the vitality structure opens up new opportunities for managing them, through a purposeful correction of their vitality structure.
Keywords: vitality, synotogenesis, autoregulation, prolonged dormancy, natural population, population-ontogenetic approach, the conservation of biodiversity.